Protection of public health in the context of the spread of coronavirus infection Covid-19 (experience of the Russian Federation) - Lukyanova, Vlada Yu. (Journal of the Belarusian State University. Law, 2021)
The spread of coronavirus infection (Covid-19), recognised by the World Health Organisation as a pandemic, has led to the adoption of unprecedented legal measures in Russia aimed at overcoming the negative consequences of the pandemic. Such measures include, among others, measures aimed at minimising the impact of the coronavirus pandemic on public health. In the Russian Federation, such measures are taken under a special legal regime – a high-alert regime. The aim of the study is to identify the capabilities of law as a regulator of social relations in the field of public health in the conditions of the pandemic coronavirus infection for the future such crises. To achieve it following tasks were solved: the analysis of the dynamics of law-making bodies of state power of the Russian Federation in the period of the pandemic was held, the measures taken to ensure public health in terms of the spread of Covid-19, including those imposed in the framework of the mode of increased readiness measures limit the constitutional rights of citizens were examined. The article presents the results of a study of the state and dynamics of Russian law-making during the coronavirus pandemic, which had a significant impact on the legal system of the Russian state. The article examines the legal nature of the high-alert regime as the main tool used by the Russian state to minimise the negative consequences of the Covid-19 pandemic, including public health issues. The article analyses the problem of the permissibility of restricting certain constitutional rights of citizens when introducing a high-alert regime. Based on the results of the study, proposals are formulated for improving the legislation on the legal regime of high readiness and on the protection of public health.